2016
DOI: 10.1016/j.chom.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Butyrate-Producing Clostridia from the Gut Microbiota Drives an Aerobic Luminal Expansion of Salmonella

Abstract: The mammalian intestine is host to a microbial community that prevents pathogen expansion through unknown mechanisms, while antibiotic treatment can increase susceptibility to enteric pathogens. Here we show that streptomycin treatment depleted commensal, butyrate-producing Clostridia from the mouse intestinal lumen, leading to decreased butyrate levels, increased epithelial oxygenation and aerobic expansion of Salmonella enterica serovar Typhimurium. Epithelial hypoxia and Salmonella restriction could be rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
604
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(679 citation statements)
references
References 50 publications
21
604
1
Order By: Relevance
“…The HIF response was rescued by butyrate supplementation. These observations were recently validated and extended to reveal that the depletion of butyrate-producing species depletes local oxygen levels and allows the expansion of aerobic luminal microbes (82). Given the multiple levels of protection afforded by HIF within the mucosa (2), such findings implicate this butyrate/HIF axis as a host/microbe crosstalk pathway wherein SCFAs promote protective signaling in the distal gut.…”
Section: Host-microbial Metabolism and Tissue Barriermentioning
confidence: 92%
“…The HIF response was rescued by butyrate supplementation. These observations were recently validated and extended to reveal that the depletion of butyrate-producing species depletes local oxygen levels and allows the expansion of aerobic luminal microbes (82). Given the multiple levels of protection afforded by HIF within the mucosa (2), such findings implicate this butyrate/HIF axis as a host/microbe crosstalk pathway wherein SCFAs promote protective signaling in the distal gut.…”
Section: Host-microbial Metabolism and Tissue Barriermentioning
confidence: 92%
“…71 In addition, a recent study illustrated that when butyrate-producing Clostridia are depleted by streptomycin treatment, epithelial oxygenation is elevated, leading to luminal expansion of Salmonella via aerobic growth mediated by Salmonella type III cytochrome bd-II oxidase and synergized with nitrate reductases. 72 A previous study showed that aerobic respiration is required for commensal and pathogenic E. coli to colonize the mouse intestine, as E. coli mutants lacking ATP synthase, which is required for all respiratory energy-conserving metabolism, were eliminated by competition with respiratory-competent wild-type strains. Likewise, E. coli mutants, which lacked the high-affinity cytochrome bd oxidase that is required for aerobic respiration when oxygen tensions are low, also failed to colonize the mouse intestine.…”
Section: Introductionmentioning
confidence: 99%
“…As with other SCFAs, butyrate is consumed by the host as an energy source; however, unlike the other common SCFAs, such as propionate and acetate, butyrate is the preferred energy source for colonocytes (2) and is rapidly absorbed and used by the colonic epithelium. This rapid oxidation of butyrate reduces local oxygen concentrations, causing the epithelia to become hypoxic and thus limiting the growth of facultative aerobic pathogens, such as Salmonella species (3,4). In addition, butyrate alters host gene expression to promote immune tolerance to the colonic microbiota and to improve the barrier function of the colonic epithelium.…”
mentioning
confidence: 99%